2009
DOI: 10.1159/000230006
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Repeated DNA Elements in the Genome of the Cichlid Fish <i>Cichla kelberi</i> and Its Contributions to the Knowledge of Fish Genomes

Abstract: Repeated DNA elements have been extensively applied as physical chromosome markers in comparative studies for the identification of chromosomal rearrangements, the identification of sex chromosomes, chromosome evolution analysis and applied genetics. Here, we report the characterization of the transposable elements (TE) Tc1, Rex1, Rex3 and Rex6 and a new element called RCk in the genome of the South American cichlid fish Cichla kelberi using nucleotide sequence analysis and hybridization to metaphase chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 102 publications
9
54
2
1
Order By: Relevance
“…10 This was confirmed by the BLASTn analysis where the Rex1 and Rex3 sequences shared high similarity with those of other fish groups, which demonstrates that these elements are fairly well conserved in different families. Previous researchers have suggested that the Rex6 element may have been lost or diverged greatly, depending on the rate of host evolution.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…10 This was confirmed by the BLASTn analysis where the Rex1 and Rex3 sequences shared high similarity with those of other fish groups, which demonstrates that these elements are fairly well conserved in different families. Previous researchers have suggested that the Rex6 element may have been lost or diverged greatly, depending on the rate of host evolution.…”
Section: Discussionsupporting
confidence: 57%
“…17 Species in the family Cichlidae are exceptional because the Rex elements are frequently distributed in the pericentromeric regions. [9][10][11][12][13][14] In particular, Rex1 had different chromosome locations in Leporinus species. Leporinus elongatus, L. macrocephalus, and L. obtusidens had isolated signals in terminal positions in all chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hybridization with the [GATA] n sequence showed correspondence with the heterochromatin in the terminal region of almost all chromosomes, also being present in lower amount in interstitial regions, and coincident with the unique C-band in the pericentromeric region (pair 1). This situation in which repetitive elements have been found widely dispersed in the genomes is relatively common and has been observed in other fish species recently (e.g., Teixeira et al, 2009;Ferreira et al, 2011).…”
Section: Discussionmentioning
confidence: 56%